Workshop report: Training and Development of Downscaled Seasonal Forecasts for Pilot Districts, Kigali, Rwanda - Siebert, Asher; Kagabo, Desire M.; Vuguziga, Floribert (2016)
This report summarizes the discussions, analysis and interactions during IRI postdoctoral research scientist Asher Siebert’s one-week stay in Rwanda in late August 2016 as part of the CCAFS-Rwanda project. The overall aim of this project is help farmers in Rwanda to be better adapted to climate variability and any climate change they may face, and, in doing so, to help improve food security and agricultural outcomes. Seasonal forecasting and downscaling methods were discussed, and a particular national forecast made with the Climate Predictability Tool (CPT) and was shared, along with downscaled results in probability of exceedance format. In country meteorology participants were trained in CPT. Further discussions addressed longer-term collaborative work on both climatology and further seasonal prediction work, particularly with regard to El Nino/Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD). Discussions with experts at CIAT and the Rwanda Agriculture Board also addressed the prospect of using the Water Requirement Satisfaction Index (WRSI) as a monitoring and climate/agriculture risk management tool in the future.